Fast and Sensitive Determination of Cadmium and Selenium in Rice by Direct Sampling Electrothermal Vaporization Inductively Coupled Plasma Mass Spectrometry - Guanyu Lan; Xue Li; Hongyu Jia; Xiaofeng Yu; Zhaohui Wang; Jijun Yao; Xuefei Mao (Molecules, 2022)
In this work, a direct solid sampling device based on modified graphite furnace electrothermal vaporization (GF-ETV) with inductively coupled plasma mass spectrometry (ICP-MS) was established for the simultaneous detection of trace selenium and cadmium in rice samples. A bypass gas was first designed in GF-ETV to improve the device’s analytical sensitivity and precision. The ashing and vaporization conditions, the flow rates of the Ar carrier and the bypass gases of ICP-MS were all investigated. Under the optimized conditions, the limits of detection (LODs) for Se and Cd were 0.5 μg kg−1 and 0.16 μg kg−1, respectively; the relative standard deviations (RSDs) of repeated measurements were within 8% (n = 6). The recoveries of Cd and Se in rice samples were in the range of 89–112% compared with the microwave digestion ICP-MS method, indicating good accuracy and precision for the simultaneous detection of Se and Cd in rice matrix. The whole analysis time is <3 min without the sample digestion process, fulfilling the fast detection of Se and Cd in rice samples to protect food safety.